Alternative Management Approaches of Citrus Diseases Caused by Penicillium digitatum (Green Mold) and Penicillium italicum (Blue Mold) - Bhatta, Usha K. (Frontiers in Plant Science, 2022)
Green mold (Penicillium digitatum) and blue mold (Penicillium italicum) are among the most economically impactful post-harvest diseases of citrus fruit worldwide. Post-harvest citrus diseases are largely controlled with synthetic fungicides such as pyrimethanil, imazalil, fludioxonil, and thiabendazole. Due to their toxic effects, prolonged and excessive application of these fungicides is gradually restricted in favor of safe and more eco-friendly alternatives. This review comprehensively describes alternative methods for the control of P. digitatum and P. italicum: (a) antagonistic micro-organisms, (b) plant extracts and essential oils, (c) biofungicides, (d) chitosan and chitosan-based citrus coatings, (e) heat treatments, (f) ionizing and non-ionizing irradiations, (g) food additives, and (h) synthetic elicitors. Integrating multiple approaches such as the application of biocontrol agents with food additives or heat treatments have overcome some drawbacks to single treatments. In addition, integrating treatment approaches could produce an additive or synergistic effect on controlling both molds for a satisfactory level of disease reduction in post-harvest citrus. Further research is warranted on plant resistance and fruit-pathogen interactions to develop safer strategies for the sustainable control of P. digitatum and P. italicum in citrus.